Explanation:
Note that this graph has roots at x = 1 and x = 5. Its maximum occurs at (3, 4) and it opens downward. So writing the vertex form of this graph, we get
![y = - (x - 1)(x - 5)](https://img.qammunity.org/2022/formulas/mathematics/college/w85lio2m8dst53wvwr2imbsgijbccmj2pt.png)
Then expanding this, the equation becomes
![y = - {x}^(2) + 6x - 5](https://img.qammunity.org/2022/formulas/mathematics/college/jn4tma3q0ry9te02mj7lwwd6xmktucsz06.png)
As a check, note that the y-intercept is at (0, -5) so if we use x = 0 in the equation above, we see that y = -5. Similarly, if we use x = 3, the value of y is y = 4, as expected.